Effects of the South Asian summer monsoon anomaly on interannual variations in precipitation over the South-Central Tibetan Plateau - Zhu, Yanxin; Sang, Yan-Fang; Chen, Deliang; Sivakumar, Bellie; Li, Donghuan (Environmental research letters, 2020)
An anomalous South Asian summer monsoon (SASM) system could generate a large anomaly in precipitation and hydrological disasters in the SASM-prevailing area, as widely reported for the Indian Peninsula. However, how the SASM system influences the precipitation anomaly over the South-Central Tibetan Plateau (SCTP) is largely unknown. In this study, we (a) analyze the influences of the early and late onset (demise) of the SASM on the interannual variations in precipitation over the SCTP during 1979-2015; and (b) illuminate the underlying mechanisms and asymmetric effects with regard to the onset and demise of the SASM by analyzing the characteristics of water vapor transport and moisture budgets in this region. Results indicate that the precipitation anomaly over the SCTP is dominated by the cyclonic and anticyclonic water vapor transport associated with the anomalous SASM activities, causing moisture convergence and divergence in this region. The topographic effect in the southeastern Tibetan Plateau (SETP) and southwestern Tibetan Plateau (SWTP) further strengthens the anomaly in water vapor transport in vertical direction and contributes to the precipitation anomaly through moisture convergence and divergence. The anomalous SASM and topography exhibit asymmetric effects between the onset and demise as well as between the early and late onset (demise) of the SASM. They cause 23.41%, 15.91%, and 1.96% difference in precipitation between the early and late SASM-onset years, and 13.05%, 21.50%, and 29.86% difference in precipitation between the early and late SASM-demise years in the SETP, central Tibetan Plateau (CETP), and SWTP, by regulating the horizontal and vertical thermodynamic and dynamic processes. The results help improve our understanding of the SASM-precipitation relationship over the SCTP and guide the prediction of precipitation and alleviation of water-related disasters in the region and its surroundings that are home to billions of people in Asia.